THE SERVICE QUALITY AND CUSTOMER VALUE IMPACT ON LOYALTY: MEDIATING ROLES OF TRUST AND SATISFACTION (STUDY AT IKAN BAKAR CIANJUR SURABAYA RESTAURANT) - Avril Angesti Arya Putri; Kristiningsih (Politeknik Ubaya, 2024)
This study investigates the impact of service quality and customer perceived value on customer loyalty, mediated by trust and satisfaction, in the context of Ikan Bakar Cianjur (IBC) Surabaya. A quantitative approach involved 116 respondents who provided data through structured surveys. The analysis, conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), reveals that service quality and perceived value significantly enhance trust and satisfaction but have a limited direct impact on loyalty. Instead, trust emerges as the key determinant of loyalty. The study underscores the importance of fostering trust and satisfaction to build long-term customer relationships and maintain competitive advantage. High service quality provides numerous advantages for a company. According to Kotler and Keller (2016), businesses that excel in service quality are likely to enjoy increased customer loyalty and a competitive edge in the marketplace. Customers who have positive service experiences are more inclined to return and recommend the business to others. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License.